Cooperative acid-base sites of solid Ba-Zr mixed oxide catalyst for efficient isomerization of glucose to fructose in aqueous medium - Shaikh, Samrin S.; Patil, Chetana R.; Kondawar, Sharda E.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
Efficient and highly selective isomerization of glucose to fructose was achieved by using the inexpensive Ba-Zr mixed metal oxide catalyst. Catalyst was prepared by varying Ba-Zr ratios using co-precipitation method. Various phases formed, planes exposed, morphology, elemental composition and particle size, basic site density and strength, oxidation state of elements were well studied by using various characterization techniques. The XRD analysis clearly indicates the presence of Ba+2 and Zr+4 in the form of BaO, ZrO2 and BaZrO3 phases. The SEM and HR-TEM images indicate that, Ba-Zr (2 : 1) catalyst prepared showed uniform morphology with spherical and rod-shaped particles ranging from 300 to 600 nm. Under the optimized reaction conditions Ba-Zr (2 : 1) catalyst exhibited excellent results in terms of 57 % of glucose conversion with 89 % selective formation of glucose. The presence of both acidic as well as basic sites play vital roles in activating the substrate molecules to selectively yield fructose. Ba-Zr (2 : 1) catalyst showed excellent recyclability performance up to four recycles.
Keywords: Co-precipitation; fructose; glucose; isomerization; mixed metal oxide